2011
DOI: 10.1007/s11695-011-0576-x
|View full text |Cite
|
Sign up to set email alerts
|

Let Loose Technique, an Option in Band Migration

Abstract: Obesity is nowadays a serious worldwide public health problem. In order to give patients a better quality of live, there are now medical and surgical treatments that may be offered to those patients. Since 2005, the Hospital de Santarém has been doing bariatric surgery. From 77 procedures with laparoscopic adjustable gastric banding, there were three cases of migration. The authors propose a new procedure to deal with migrations, according to a classification for band migration, as an alternative to a removal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…2,9,10 Other possible causes for gastrointestinal obstruction associated with laparoscopic gastric banding include erosion and retrograde migration to the gastroesophageal junction 18 or external stenosis due to the band tubing. 19 Uncomplicated erosion mostly is a non-life-threatening condition, and after disconnection of the port from the catheter, there are several therapeutic options, including laparoscopic 20 and endoscopic salvage or the "let loose technique," 21 to await natural passage of the band itself. Whatever approach is chosen, periodic clinical assessments of the patient, including repeated conduction of x-ray and/or endoscopy, are crucial to ensure an uncomplicated outcome.…”
Section: Discussionmentioning
confidence: 99%
“…2,9,10 Other possible causes for gastrointestinal obstruction associated with laparoscopic gastric banding include erosion and retrograde migration to the gastroesophageal junction 18 or external stenosis due to the band tubing. 19 Uncomplicated erosion mostly is a non-life-threatening condition, and after disconnection of the port from the catheter, there are several therapeutic options, including laparoscopic 20 and endoscopic salvage or the "let loose technique," 21 to await natural passage of the band itself. Whatever approach is chosen, periodic clinical assessments of the patient, including repeated conduction of x-ray and/or endoscopy, are crucial to ensure an uncomplicated outcome.…”
Section: Discussionmentioning
confidence: 99%
“…BE can be partial or complete with intragastric migration of the band [4]. When completely internalized into the gastric lumen, the band has the potential to migrate into the small bowel [[5], [6], [7], [8], [9]]. Biliary obstruction is a very rare complication that may result from intrajejunal band migration.…”
Section: Introductionmentioning
confidence: 99%
“…Our patient was found to have gastric erosion and LAGB migration into the proximal jejunum, causing small bowel obstruction and requiring laparoscopic removal of the gastric band. A review of the literature revealed previous reports of cases in which laparotomy and open removal had been undertaken [2], as well as disconnection of the connection tubing and allowing passage out through the gastrointestinal tract in the so-called let loose technique [3].…”
mentioning
confidence: 99%